1993
DOI: 10.1039/ft9938900707
|View full text |Cite
|
Sign up to set email alerts
|

Self-association of octan-1-ol in the pure liquid state and in decane solutions as observed by viscosity, self-diffusion, nuclear magnetic resonance and near-infrared spectroscopy measurements

Abstract: The self-association of octan-1-01 in the pure liquid state and in decane solutions has been studied by nearinfrared spectroscopic observation over the temperature range 298.1-348.1 K and also by viscosity, self-diff usion and NMR measurements. The absorption bands assigned to the hydroxy group are superimposed on several bands attributed to the methylene groups belonging to both the alcohol and decane molecules. A superior technique using a computer was adopted for the cancellation of the absorption bands due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 13 publications
8
70
0
1
Order By: Relevance
“…Provided the distribution of the aggregation number is small, N 2 /N is practically equal to N . Figure 7 shows that the values N 2 /N is close to the aggregation number expected for alcohols in nonpolar solvents [4,7,8], although it is not a constant value and is a little larger than the expected one.…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…Provided the distribution of the aggregation number is small, N 2 /N is practically equal to N . Figure 7 shows that the values N 2 /N is close to the aggregation number expected for alcohols in nonpolar solvents [4,7,8], although it is not a constant value and is a little larger than the expected one.…”
Section: Resultsmentioning
confidence: 55%
“…Now the total differential dm r is written as a function of T , p, and m by using Eqs. (4) and (16), and then dm a = r=2 dm r is also written as…”
Section: Thermodynamics Of Aggregate Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that rings composed of about 4 or more members contribute to A(λ δ ) (Ref. 56) and then would tend to increase the calculated 〈n〉.…”
Section: A Average Cluster Size Of Alcohol Aggregatesmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] However, until recently, [9][10][11][12][13][14][15][16][17][18][19][20] the NIR investigations were not always satisfactory in the quantitative aspect; there was no reliable method for determining precisely the intensities of key bands such as the first overtones of OH and NH stretching modes. Recent rapid progress both in hardware and software for NIR spectroscopy has brought about innovative changes in the NIR studies of self-associated compounds.…”
Section: Introductionmentioning
confidence: 99%